2020
DOI: 10.1002/cbic.202000536
|View full text |Cite
|
Sign up to set email alerts
|

Stronger Together: Multivalent Phage Capsids Inhibit Virus Entry

Abstract: Antivirals are now more important than ever. To efficiently inhibit virus replication, antiviral multivalent strategies need sufficient affinity to overcome the excellent matching between the virus and its receptor. This report highlights a phage capsid scaffold strategy that can be used to precisely position sialic acid moieties to inhibit influenza A virus replication

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…In targeting influenza A virus replication by competitive blocking of the virus and cell carbohydrate interaction, Gallego et al 99 reported the precise position of sialic acid moieties (ligand) utilising the phage (Bacteriophage Qβ) capsid scaffold strategy to achieve the structurally defined positioning of sialic acid matching the binding site of trimeric hemagglutinin of the virus. Following the identification of a capsid residue spaced 5–6 nm on the particle surface, close to the sialic acid binding site of hemagglutinin, the expression in the presence of l -homopropargylglycine introduced a propargyl group using azide-alkyne cycloaddition and different linkers to anchor the sialic acid ligands.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…In targeting influenza A virus replication by competitive blocking of the virus and cell carbohydrate interaction, Gallego et al 99 reported the precise position of sialic acid moieties (ligand) utilising the phage (Bacteriophage Qβ) capsid scaffold strategy to achieve the structurally defined positioning of sialic acid matching the binding site of trimeric hemagglutinin of the virus. Following the identification of a capsid residue spaced 5–6 nm on the particle surface, close to the sialic acid binding site of hemagglutinin, the expression in the presence of l -homopropargylglycine introduced a propargyl group using azide-alkyne cycloaddition and different linkers to anchor the sialic acid ligands.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…Multivalent interactions are widespread in nature and play important roles in biological processes, such as cell adhesion, growth regulation, , bacterial and viral infections, immune regulation and response, and DNA transcription . Multivalent carbohydrate–protein interactions are the key processes in a plethora of critical biological functions, including the adhesion of the influenza virus to cell membranes, the targeting cell recognition of carbohydrates with membrane receptors, and the immune response of carbohydrates with macrophages and dendritic cells. Novel therapeutic drugs based on multivalent carbohydrate–protein interactions have seen rapid development and clinical application in recent years, such as GalNAc-siRNA for hepatic targeting with the asialoglycoprotein receptor (ASGPR) and lysosome-targeting chimera (LYTAC) technology based on mannose-6-phosphate and GalNAc derivatives.…”
Section: Introductionmentioning
confidence: 99%